594 HIDDEN CAUSES FOR UNEXPLAINED SINCOPE. (15th December 2022) - Costantino, Roberto; Napoli, Gianluigi; Piscitelli, Laura
Abstract: Bicuspid aortic valve (BAV) is a congenital cardiac abnormality, affecting approximately 1%-2% of the general population (male > female). A 33-year-old man was admitted to emergency department (ED) for syncope during exertion. He had a history of cigarette smoking with a known previously discovered BAV with mild stenosis. TTE showed a severely calcified bicuspid aortic valve with severe stenosis and regurgitation. ECGs showed frequent asymptomatic complete hearth block (CHB), unresponsive to isoprenaline infusion. He underwent ministernotomy aortic valve replacement (AVR) with mechanical valve. During hospital stay, the 24h ECG telemetric monitoring did not show any A-V disturbance and TTE demonstrated normal prosthesis function. Pacemaker implantation was delayed, Follow-up was performed at 1, 6 and 10 months after surgery: 24h-ECG recordings were performed showing no A-V conduction disturbances. At 1 year, during routine medical screening, cardiac frequency of 38 bpm was detected (ECG revealed sinus rhythm with CHB and junctional escape rhythm of 38 bpm). ICCU echocardiogram showed good ventricular and prosthesis function. Therefore, a dual-chamber MRI compatible pacemaker was implanted. Few cases are reported in literature of young patients presenting with A-V block having a severely calcified aortic bicuspid valve. Their management is poorly explored, and therapies (medical therapy, aortic valve replacement and pacemaker implantation) are not fully evidence based. In literature, 3 cases of possible reversibility of conducting system disorders after severe stenotic aortic valve surgery are described. Noninvasive strategy was initially successful as demonstrated by both the post-operative absence of any AV conduction disturbance and/or symptoms and the close follow-up monitoring. Despite of previous evidence, our experience demonstrates that a complete heart block can recur following aortic valve surgery, even in young patients. Initial presentation of CHB was intermittent, suggesting that the structural damage to the conducting system could not be irreversible; thus, it could positively respond to valve surgery. Unfortunately, in CHB with calciﬁc aortic stenosis patients should be considered for PM implantation at the time of aortic surgery. When a waiting strategy prevails, especially for young patients, close monitoring and follow-up must be warranted to early detect A-V disturbances recurrence.